Specific Detection of Serum Antibodies against BKPyV, A Small DNA Tumour Virus, in Patients Affected by Choroidal Nevi - Pietrobon, Silvia; Bononi, Ilaria; Lotito, Francesca; Perri, Paolo; Violanti, Sara; Mazzoni, Elisa; Martini, Fernanda; Tognon, Mauro G. (Frontiers in Microbiology, 2017)
ABSTRACT Ocular or choroidal nevus (CN) is a rare benign neoplastic lesion of the eye. The cause of CN onset/progression, which arises from the transformation of ocular melanocytes, is not known. A fraction of CN patients may develop uveal melanoma. The objective of this study was to investigate the association between CN and BK polyomavirus (BKPyV), a small DNA tumour virus. Serum IgG antibodies which react with BKPyV antigens were analysed. A indirect E.L.I.S.A. using synthetic peptides that mimic BKPyV antigens was employed. Serum antibodies against BKPyV were also investigated by haemagglutination inhibition (HAI) assay. Sera were from CN patients and healthy subject (HS) were the control. A statistically significant higher prevalence of antibodies against BKPyV capsid protein antigens in serum samples from CN patients was detected, compared to HS, using two independent techniques, indirect E.L.I.S.A. and HAI (87.3% CN vs. 62.1% HS and 91.5% CN vs. 64.4% HS, respectively; p<0.005). Our data suggest an association exists between CN and BKPyV indicating that this small DNA tumour virus could be responsible in the onset of this benign neoplastic lesion affecting eye melanocytes. This investigation reports the association between choroidal nevi and BKPyV infection for the first time. These data are innovative in this field and may represent a starting point for further investigation into the putative role of BKPyV in CN onset/progression.